Penegakan Hukum atas Tindak Pidana Kekerasan yang Dilakukan Anak di Wilayah Hukum Polresta Yogyakarta - Muhammad Yogie Adha (Lex Renaissance, 2020)
Cases that involve children as perpetrators of violence have increased sharply year by year. This phenomenon is interesting to study, especially to examine the common thread, find the root of the problem, and see how the law enforcement process is and what obstacles are faced by the Yogyakarta City Police. The research method used is qualitative field research. The results of the study concluded that the law enforcement process carried out by the Yogyakarta City Police was always guided by the Law, but still needed improvements in the applicable Law.